The Empowerment of The Cyber Communities By The Indonesian Goverment From The Perspective of Total War Strategy - Devis Lebo; Syaiful Anwar (Syntax Corporation Indonesia, 2023)
The development of Information Technology and Computers (ICT) has made changes that affect the concept of security. The impact of these ICT developments poses a cyber threat to the National Critical Information Infrastructure (IIKN). The cyber community empowerment effort aims to help the government, institutions and private parties related to the ICT sector in safeguarding and securing IIKN from cyber attacks whose impact can collapse a country if it is not anticipated earlier. For that we need a strategy that is able to support the empowerment of the cyber community by the government in the perspective of universal war. In writing this article, the author uses a method by collecting data and information through the help of various materials contained in the literature (books) or also known as the type of phenomological research associated with qualitative descriptive. From the results of the literature research that the authors get, it is known that the cyber community has not fully helped the government in national defense, there are some cyber communities that have not been involved, it takes the role of government, institutions and private parties related to ICT to be able to realize cyber community empowerment by the Government in the perspective of Total war.